Challenges in The Academic Promotion Process: Perspectives From Faculty Members - Maulindar, Joni; Awang Long, Zalizah; Che Mustapha, Jawahir; Purnomo, Singgih (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The academic promotion process faces various challenges that cause delays for faculty members in reaching higher ranks. This research aims to identify and analyze the factors contributing to delays in the academic promotion process. The research method used is a quantitative approach, with data collection techniques involving the distribution of questionnaires to faculty members who are currently undergoing or about to undergo the academic promotion process. The research results indicate that the lack of transparency in rules, policy changes, evaluation complexity, communication limitations, and institutional support all have a significant and equal impact on the challenges of academic promotion, with each factor having a coefficient of 0.2000. The R-squared and Adjusted R-squared values of 1.000 indicate that this model can explain the entire variation in academic promotion challenges. The high statistical significance of all coefficients suggests that these results are almost certainly not due to chance. Data analysis also shows that there is little autocorrelation in the model's residuals, and the residual distribution is nearly normal. These findings highlight the importance of transparency, policy consistency, effective communication, and institutional support in the academic promotion process. Improvements in these areas are expected to reduce the challenges faced by faculty members during the promotion process